79 Increased Matrix Production In Tendon Constructs Derived From Older Stem Cells. (5th September 2014) - Peffers, Mandy; Clegg, Peter
Abstract : Introduction: Mesenchymal stem cells (MSCs) have prospective applications in regenerative medicine and tissue engineering, demonstrating promising results (Mazzocca, 2010). In particular they represent an attractive possibility for tendon repair and regeneration (Butler, 2008). A number of studies have used MSCs to make tendon-like constructs in-vitro (Butler, 2010; Kapacee, 2010). Furthermore the principles of tissue engineering involve a complex interplay of factors (Kennard, 2011) and there is some question as to what extent these cells are subject to ageing. Consequently, any loss in functionality with age would have profound consequences for the maintenance of tissue viability and the quality of tissues. The capacity of MSCs to differentiate into various types of tissue seems to change with age (Ross, 2000). However no studies have been undertaken on age-related effects on differentiation potential into tendon. This study aims to evaluate the proteome of tendon constructs synthesised from young and old MSCs. Methods: MSCs at passage 4 from young; n = 15 (22.2 years ± 2.3 SD) and old; n = 6 (64.8 years ± 6.6 SD) human donors were used to make tendon constructs as previously described (Kapacee, 2010). These were harvested after 28days. Tenogenic differentiation was assessed using histology, electron microscopy (EM) and quantitative real-time PCR. Following protein extraction from the constructs using 0.1% Rapigest™ and tryptic digestion, peptides were identified using liquid chromatography mass with a linear ion-trap Orbitrap mass spectrometer. Using Progenesis™ LC-MS the top 5 spectra were exported for database searching in PEAKS ® 7 against the Unihuman database. Proteins were identified with a false discovery rate of 1% and a minimum of 2 peptides per protein. The resulting peptide-spectrum matches were imported into Progenesis™ LC-MS for label-free relative quantification. Pathway analysis was undertaken using Ingenuity Pathway Analysis. Results: A tenogenic phenotype was demonstrated by an increase in collagen 1 alpha 1, scleraxis and thrombospondin 4 gene expression in tendon constructs compared to undifferentiated MSCs. In addition collagen fibril formation was demonstrated using Masson's Trichrome staining and brightfield microscopy or EM. There were no gross differences in histology between constructs from young and old MSCs. A total of 1401 proteins (young) and 1971 proteins (old) were identified, 207 with a greater than 2 fold change and false discovery adjusted p value <0.05; 201 higher in constructs from old MSCs and 6 lower in old. Those enriched in old included cartilage oligomeric matrix protein, biglycan, lumican, collagens IV and XII, matrix metalloproteinases 2, 14 and tissue inhibitors of metalloproteinases 1 and 3. Pathway networks including carbohydrate metabolism, glycolysis, gluconeogenesis, protein ubiquitination, and metabolism of proteins suggest an up regulation in energy metabolism and increased protein turnover in constructs derived from older donors. In addition upstream regulators identified included transforming growth factor B1 (TGFβ1), interleukin 1β (IL1β) and SMAD3. Discussion: In tendon constructs derived from older MSCs there is evidence for increased energy metabolism, and matrix deposition and turnover. Interestingly SMAD3was identified as an upstream regulator; a critical regulator of tendon formation and protein expression especially matrix proteins. This together with an increase in a number of matrix proteins implies that constructs made from older MSCs may have the capacity to produce constructs with improved matrix. The increase in proteases may suggest increased turnover. Further work is required to determine what these protein changes mean to the mechanical competence of the constructs. References: Butler et al . J Orthop Res 2008;26(1):1–9 Kapacee et al . Matrix Biol 2010;29:668–677 Kennard et al . Open Orthop J 2011;5(2):249–252 Mazzocca et al . Am J Sport Med 2010;38(7):1438–1447 Ross et al . Science 2000;289(5481):950–953